Enhancing Teacher Pedagogical Competence through the Sister School Program: An Implementation Study - Baya’gub, Rusydi; Zaini Al –Haj, Zainuddin (Tadbir : Jurnal Studi Manajemen Pendidikan, 2025)
Teacher pedagogical competence is paramount for elevating educational standards. Despite its importance, many educators still require significant development in this area. The Sister School Program, involving inter-school collaboration, offers an innovative and potentially effective strategy to address this gap. This study investigates the implementation of the Sister School program at SMA Muhammadiyah 3 Jember with the primary goal of examining its effectiveness in enhancing the pedagogical competencies of the participating teachers. Employing a qualitative, phenomenological approach, data were collected through in-depth interviews with teachers who participated in the program. The collected data were analyzed using thematic analysis to uncover the core experiences of the instructors. The findings indicate that the Sister School program significantly enhanced the teachers' pedagogical competencies, particularly fostering the adoption of more creative and engaging teaching techniques. Furthermore, participation resulted in increased teacher motivation and professional confidence in instructional delivery. Beyond individual development, the program also notably improved inter-school collaboration and knowledge sharing. In conclusion, the Sister School program at SMA Muhammadiyah 3 Jember has proven to be an effective model for enhancing teacher pedagogical proficiency. This successful implementation provides a valuable blueprint for other educational institutions seeking to improve teacher competence in similar developing contexts.